Relationship between Knowledge Level and Family Support with Covid-19 Vaccine Compliance - Nita Tri Wulandari; Mulyaningsih Mulyaningsih (JURNAL PROTEKSI KESEHATAN, 2022)
Compliance with the Covid-19 vaccine is the compliance or attitude of the community to fulfill the recommendations of health workers without coercion from any party and Compliance is individual behavior (for example: making lifestyle changes) following recommendations to complying with plans Factors that significantly influence compliance are the level of knowledge and family support . It consists of the independent variables, namely the level of knowledge and family support, for the dependent variable is compliance with the Covid-19 vaccine. This type of quantitative research with correlational design and cross-sectional design. The sampling technique used purposive sampling, with a population of 323 respondents for a sample of 84 respondents. The results of the study using the Cji Square test obtained p = 0.000 so that it can be concluded that there is a strong relationship between the level of knowledge and compliance with the Covid-19 vaccine and for the results of research using the Fisher Exact, p = 0.021 so that it can be concluded that there is a relationship between family support and compliance with the Covid-19 vaccine in Pomahan Hamlet, Senting Village, Sambi District. There is a relationship between the level of knowledge and compliance with the Covid-19 Vaccine and There is a strong relationship between family support and Covid-19 Vaccine Compliance in Pomahan Hamlet, Senting Village, Sambi District.